Smart, programmable and responsive injectable hydrogels for controlled release of cargo osteoporosis drugs - Konstantinos E. Papathanasiou (Nature Portfolio, 2017)
Abstract Easy-to-prepare drug delivery systems, based on smart, silica gels have been synthesized, characterized, and studied as hosts in the controlled release of bisphosphonates. They exhibit variable release rates and final % release, depending on the nature of bisphosphonate (side-chain length, hydro-philicity/-phobicity, water-solubility), cations present, pH and temperature. These gels are robust, injectable, re-loadable and re-usable.